Penerapan Model STAD Berbantuan Media Pop Up Book pada Pembelajaran Bahasa Indonesia Kelas III SD Negeri 78 Lubuklinggau - Marselina, Anita; Dodik Mulyono; Tri Juli Hajani (Linggau Jurnal Language Education and Literature, 2022)
ABSTRACT The purpose of this study was to determine the completeness of Indonesian language learning outcomes for third grade students of SD Negeri 78 Lubuklinggau through the application of the STAD model assisted by Pop Up Book media. This type of research is a quasi-experimental, with a one group pre-test post-test design. Based on data testing, it can be concluded that there is a significant relationship between the results of the pre-test and the results of the post-test in the application of the STAD model assisted by Pop Up Book media in learning Indonesian for third grade students of SD Negeri 78 Lubuklinggau. This can be seen from the results of the calculation of the z test hypothesis test, it is known that the value of Zcount = 3.75 is greater than Ztable with a significant level of = 0.05 obtained Ztable = 1.64 or Zcount Ztable or 3.75>1.64 then Ho is rejected and Ha is accepted. Thus, the hypothesis that the author proposes in the study is proven true, namely through the application of the STAD model assisted by the Pop Up Book media, the results of learning Indonesian language for third grade students of SD Negeri 78 Lubuklinggau can significantly achieve completeness.